South African Podocarpaceae distribution interpreted from a physiological and population genetics perspective - Twala, Thando Caroline (University of the Witwatersrand, Johannesburg, 2023)
Podocarpaceae (podocarp) are the most diverse conifer family with a Southern Hemisphere distribution. Podocarps occur in Afrotemperate and Afromontane forests at high elevations that are cool and humid. Podocarps once dominated the forest canopy but due to their slower growth rate and photosynthetic rates they have are in competition withangiosperms which have faster growing and higher photosynthetic rate. Due to the competition between podocarps and angiosperms, Bond (1989) proposed that podocarps were excluded to nutrient poor and unfavourable environments due to their limited competitive ability. However, podocarps persist under the forest canopy until conditions become favourable. This power dynamic shifts with climate oscillations where podocarps distributions expand and dominate when conditions become cooler. Owing to podocarps being the most diverse and widespread conifers they make for a good study system. This thesis focuses on understanding the climatic variables driving the current and future distribution of podocarps, how their seedling physiology may influence their ability to recruit and establish under climate change, and how this can influence their ability to disperse in their South African distribution. Ensemble species distribution modelling was used to characterise the current and future distribution of podocarps and identify the climatic variables that influence their distribution. The current and future environmental niche was quantified using environmental niche modelling. I found that variables predicting rainfall seasonality were the most important at determining the distribution of podocarps in South Africa. Afrocarpus falcatus and P. latifolius were predicted to have the largest geographic distribution, with P. henkelii and P. elongatus having restricted distributions. Both A. falcatus and P. latifolius were predicted to occur in the Limpopo, Mpumalanga, KwaZulu-Natal, Eastern Cape and Western Cape provinces of South Africa. Podocarpus henkelii was predicted to occur in the KwaZulu-Natal and Eastern Cape provinces. Podocarpus elongatus is endemic to the Western Cape Province. All four podocarps were predicted to expand to higher altitudes (up the escarpment) under climate change and contract in its coastal distribution. Although P. elongatus was predicted to occupy the smallest geographic distribution it was predicted to have the widest environmental niche than the other species, which was predicted to contract under climate change. The environmental niche of P. latifolius and P. henkelii was predicted to remain stable. Afrocarpus falcatus, P. latifolius, and P. henkelii showed niche conservatism, however, P. elongatus under RCP 4.5 → current and the RCP 8.5↔ current niche comparisons showed niche divergence. Podocarpus elongatus was predicted to expand to an environment it currently does not occupy. Ecophysiological and morphological experiments were conducted to understand how podocarp seedlings respond to drought and elevated temperatures. The experiments indicated that P. henkelii seedlings were more drought and heat tolerant than A. falcatus seedlings. Conditions are predicted to become hotter and drier in some parts of South Africa, and this study has shown that P. henkelii seedlings will be able to tolerate these conditions better than A. falcatus seedlings. Furthermore, this suggests that the distribution of P. henkelii is not constrained by its physiology but rather by other mechanisms such as competition, reproductive biology, and/or shade tolerance. Microsatellites were used to inform us about possible podocarp dispersal patterns in A. falcatus, P. latifolius and P. henkelii in South Africa. The results suggested that podocarp populations in South Africa were shown to have higher genetic diversity than other podocarps globally, however these results may be due to the limited number of microsatellites used in this study, smaller population sizes in comparison to other studies and methods used to measure population structure and diversity. As expected, the geographically widespread species (A. falcatus and P. latifolius) are more diverse than the geographically restricted P. henkelii. Geographically distant A. falcatus and P. henkelii populations showed higher differentiation than geographically proximal populations. In P. latifolius South African populations, there was strong isolation by distance. Although the distribution of podocarps is disjunct, there is dispersal between populations. Podocarps are resilient to climate change as was demonstrated by the work in this thesis, and by their paleodistribution expanding and contracting with climate oscillations. In this thesis I considered climate, ecophysiology and genetics as determinants of podocarps distribution. Under climate change, podocarps are predicted to expand to higher elevations to track favourable climatic conditions. Seasonal drought is the most important climatic determinant of podocarp distribution. The ability of these species to tolerate drought and heat stress suggests that the seedlings might be able to tolerate short periods of drought and heat stress, however prolonged exposure may lead to seedling mortality, but populations will then be maintained by adults. Populations show evidence of gene flow, indicating they will be able to persist through changing climates, as they have done in the past. This thesis has highlighted that the factors constraining podocarp distributions might be demographic, and future works should investigate the role of fire in podocarp seedling establishment and longevity, as well as their interactions with angiosperm competitors.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Climate change; Dispersal; Distribution; Drought stress; Ecophysiology; Environmental niche; Heat stress; Morphology; Podocarp; Population genetics; Species distribution modelling; UCTD; SDG-13: Climate action